Travel Writing and the Transnational Author - Knowles, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Travel Writing and the Transnational Author explores the travel writing and transnational literature of four authors from the 'postcolonial canon': Michael Ondaatje, Vikram Seth, Amitav Ghosh, and Salman Rushdie.
Keywords: Literature .; Fiction; Literature—Philosophy.; Culture—Study and teaching; Oriental literature; Postcolonial/World Literature; Fiction; Literary Theory; Cultural Theory; Asian Literature